PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN DALAM RUMAH TANGGA (STUDI PUTUSAN PENGADILAN NEGERI LUBUK PAKAM NOMOR: 749/PID.SUS/2023/PN Lbp) - Yosua Sitio, Ignasius Obin; Munthe, Riswan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study examines the forms of legal protection for victims of domestic violence, which is a long-standing social phenomenon and remains a significant issue in Indonesia, particularly affecting women. The home is not only a place of residence but also serves as the primary protection in the process of individual development. However, internal family conflicts often trigger domestic violence, impacting the physical and psychological conditions of the victims. This research is a normative juridical study using a statutory approach and a case approach. Data collection was conducted through literature review, document study, observation, and interviews. The analysis was carried out qualitatively to draw conclusions aligned with the issues studied. The study focuses on the forms of legal protection available for victims of domestic violence in Indonesia and the effectiveness of institutions in protecting victims in handling domestic violence cases. This research is based on the Lubuk Pakam District Court Decision Number: 749/Pid.sus/2023/PN.lbp. While the decision is considered appropriate, the author argues it is still inadequate due to the absence of definite protection for victims of domestic violence, especially women. The role of institutions in this decision is limited to processing the criminal acts committed by offenders.